Exercise-induced anaphylaxis and antileukotriene montelukast - Gajbhiye, Sapna (J Pharmacol Pharmacother, 2015)
We report a rare case of exercise-induced anaphylaxis (EIA), occurring exclusively with exercise, without any other associated trigger, detected in the prodromal phase, and prevented from additional anaphylaxis episodes by treatment with cetirizine and 10 mg daily of antileukotriene montelukast to date. EIA is a syndrome in which patients experience a spectrum of the symptoms of anaphylaxis ranging from mild cutaneous signs to severe systemic manifestations such as hypotension, syncope, and even death after increased physical activity. Many people have triggers, such as, a variety of foods, various medications, alcohol, cold weather, humidity, and seasonal and hormonal changes along with exercise that cause the symptoms. Typically, either exercise or the specific trigger alone will rarely cause symptoms. It is differentiated from cholinergic urticaria by the absence of response to passive body warming and emotional stress.